Non-linear finite element analysis of reinforced concrete deep beam with web opening - Ferry Alius; Bambang Piscesa; Faimun Faimun; Harun Alrasyid; Data Iranata (Institut Teknologi Sepuluh Nopember (ITS), 2020)
The use of Reinforced Concrete (RC) deep beams in the building may require web openings or holes for electricaland mechanical utility passage. This web opening will change the behavior of the RC deep beam and may result in early crackseven at service load. Hence, it is important to use a suitable tool to predict the full response of the RC deep beam with theopening. For that purpose, a nonlinear finite element method using 3D-NLFEA software package which utilizes a plasticityfracture model is used to predict the behavior of RC deep beam. One deep beam specimen available in the literature isinvestigated. To study the effect of using structured and unstructured mesh, as well as different element types on the loaddeflection curve, the hexahedral and tetrahedral solid element was used. From the comparisons, it was observed that the crackpattern between two different meshes was not similar. Structured mesh often has straighter crack propagation compared to theunstructured mesh. The load-deflection curve for both models is similar and both models were performed satisfactorily inpredicting the peak load of the deep beam.